(untitled) (Progressive Agriculture, 2013)
A cross section survey was carried out during the period from April to September, 2009 in different villages of Bogra district in Bangladesh to know the prevalence of ticks and lice in relation to age, sex, breed and body condition of cattle. Out of 250 randomly selected cattle, 142 (56.8%) were found infested with one or more species of ticks and lice. Among ticks, the prevalence rate was highest in case of Haemaphysalis bispinosa (31.2%) followed by Rhipicephalus sanguineus (29.2%), Boophilus microplus (27.2%) and only one species of louse Haematopinus eurysternus (23.2%). The range of parasitic burden was 1 to 16 per four square inch of heavily infested area of affected cattle. Mean parasitic burden was high in case of Haematopinus eurysternus (4.71 ± 0.35) followed by Rhipicephalus sanguineus (4.56 ± 0.29), Boophilus microplus (4.25±0.15) and Haemaphyalis bispinosa (2.85 ± 0.17). Results indicated that prevalence was significantly (P<0.01) higher in young cattle aged >1-3 years (68.0%) than calves aged ?1 year age (46.15%) and adults aged >3 years (45.2%). Infestation of tick and lice was significantly higher (P<0.05) in female (64.63%) than the male (41.86%). Infestation was more prevalent in local (72.32%) breed than the crossbred (44.2%) cattle. Cattle with poor body condition were found to be significantly (P<0.01) more vulnerable to such parasitic infestation than of cattle having normal body condition. It is concluded that tick and lice prevalence is alarming and threatening to the cattle population and host determinants play a vital role in the frequent occurrence of these ectoparasites in the study area. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16468 Progress. Agric. 22(1 & 2): 65-73, 2011